Business Intelligence with Databricks SQL : Concepts, Tools, and Techniques for Scaling Business Intelligence on the Data Lakehouse - Gupta, Vihag (Packt Publishing, Limited, 2022)
Master critical skills needed to deploy and use Databricks SQL and elevate your BI from the warehouse to the lakehouse with confidence Key Features Learn about business intelligence on the lakehouse with features and functions of Databricks SQL Make the most of Databricks SQL by getting to grips with the enablers of its data warehousing capabilities A unique approach to teaching concepts and techniques with follow-along scenarios on real datasets Book Description In this new era of data platform system design, data lakes and data warehouses are giving way to the lakehouse - a new type of data platform system that aims to unify all data analytics into a single platform. Databricks, with its Databricks SQL product suite, is the hottest lakehouse platform out there, harnessing the power of Apache Spark"! Delta Lake, and other innovations to enable data warehousing capabilities on the lakehouse with data lake economics. This book is a comprehensive hands-on guide that helps you explore all the advanced features, use cases, and technology components of Databricks SQL. You'll start with the lakehouse architecture fundamentals and understand how Databricks SQL fits into it. The book then shows you how to use the platform, from exploring data, executing queries, building reports, and using dashboards through to learning the administrative aspects of the lakehouse - data security, governance, and management of the computational power of the lakehouse. You'll also delve into the core technology enablers of Databricks SQL - Delta Lake and Photon. Finally, you'll get hands-on with advanced SQL commands for ingesting data and maintaining the lakehouse. By the end of this book, you'll have mastered Databricks SQL and be able to deploy and deliver fast, scalable business intelligence on the lakehouse. What you will learn Understand how Databricks SQL fits into the Databricks Lakehouse Platform Perform everyday analytics with Databricks SQL Workbench and business intelligence tools Organize and catalog your data assets Program the data security model to protect and govern your data Tune SQL warehouses (computing clusters) for optimal query experience Tune the Delta Lake storage format for maximum query performance Deliver extreme performance with the Photon query execution engine Implement advanced data ingestion patterns with Databricks SQL Who this book is for This book is for business intelligence practitioners, data warehouse administrators, and data engineers who are new to Databrick SQL and want to learn how to deliver high-quality insights unhindered by the scale of data or infrastructure. This book is also for anyone looking to study the advanced technologies that power Databricks SQL. Basic knowledge of data warehouses, SQL-based analytics, and ETL processes is recommended to effectively learn the concepts introduced in this book and appreciate the innovation behind the platform